Perforated diverticulitis causing necrotizing fasciitis of the lower limb - Aguiriano Casanova, María del Mar; Ponce Villar, Úrsula; Peiró Monzó, Fabián; Montesinos, Carmen; Seguí, Jesús (Cirugía del Uruguay, 2022)
A 59-year-old woman with a history of colon diverticulosis, who presented with pain in the groin region and in the left lower limb of two months of evolution. In the first instance, the patient presented with symptoms of sepsis and an erythema was observed in the left lower limb, associated with cellulitis and subcutaneous crepitus. The CT scan showed an air-fluid collection in the psoas and retroperitoneum that ascends to the abdominal cavity, finding perforated diverticulitis. Surgical treatment was based on drainage of the retroperitoneal collection and sigmoidectomy, followed by fasciotomy, debridement, and washing of the thigh. The perforation of a diverticulum can form an intraperitoneal abscess developing a peritonitis or a retroperitoneal abscess, resulting in a bacterial translocation towards the lower limb, due to the communication existing in the crural ring, generating a necrotizing fasciitis of the limb.